Debate as a Tool to Enhance Motivation and Confidence in English Learning for Non-Philology Students - Khimmataliev Dustnazar Omonovich; Yusupova Shirinoy Ortiqali Qizi (Journal of Education and Teacher Training Innovation, 2025)
This conceptual study examines the theoretical framework and practical implementation of debate activities as pedagogical tools to enhance motivation and confidence levels among non-philology students learning English as a foreign language. A comprehensive theoretical analysis was conducted, drawing on established second language acquisition theories, educational psychology frameworks, and existing empirical research on debate-based language instruction. The analysis synthesized findings from Gardner's socio-educational model, Dörnyei's L2 Motivational Self System, and task-based language teaching principles. The theoretical framework demonstrates that debate activities address non-philology students' instrumental motivation by providing authentic professional communication contexts while building confidence through structured practice opportunities. The analysis reveals three primary mechanisms: relevance to academic disciplines, scaffolded communicative practice, and development of transferable professional skills. Debate activities offer a theoretically-grounded pedagogical approach that aligns with non-philology students' learning needs and motivational orientations. This conceptual analysis requires empirical validation through controlled studies measuring actual motivation and confidence gains.